ERS differences between stroke patients and healthy controls after hand movement - Kim, Suji; Kim, Laehyun; Lee, Jonghwan (2016 4TH INTERNATIONAL WINTER CONFERENCE ON BRAIN-COMPUTER INTERFACE (BCI), 2016)
Rehabilitation after a stroke is important as the accompanying impairment has a heavy influence on the patients' quality of life and their careers. The use of a brain-computer interface (BCI) based on electroencephalography (EEG) can be one of the effective solutions for fast rehabilitation because it has certain advantages as compared to the traditional treatment. It can provide a quantitative analysis and neuro-feedback that can promote patient recovery by neuroplasticity. In this study, we investigated the correlation between the degree of motor impairment in the case of a chronic stroke and the timing of event-related synchronization (ERS) after a hand movement in order to examine the use of ERS as an assessment feature for the degree of motor impairment. Consequently, we found that after a hand movement, ERS occurred earlier in the healthy control group than in the stroke patient group. The difference between stroke patients and healthy controls was statistically significant. Further, we observed the same trend in two patient groups when stroke patients were divided into two groups according to their degree of motor impairment although the difference in this case was not statistically significant. ERS occurred earlier in the patient group with mild impairment than in the patient group with severe impairment.